Randomised controlled trial to compare the diagnostic yield of positron emission tomography CT (PET-CT) TARGETed pleural biopsy versus CT-guided pleural biopsy in suspected pleural malignancy (TARGET trial) - de Fonseka, Duneesha (BMJ Open Respir Res, 2018)
INTRODUCTION: Pleural malignancy, particularly malignant pleural mesothelioma (MPM) is increasing in incidence due to the long latency period from exposure to asbestos to development of the disease. MPM can be challenging to diagnose. For patients presenting without a pleural effusion, CT-guided biopsy remains the primary choice of biopsy, but the diagnostic sensitivity of this investigation is 70%–75%. Therefore, a proportion of patients will go on to require further biopsies. If the first biopsy is non-diagnostic, the chances of further non-diagnostic biopsies are high in MPM. METHODS: Target is a multicentre randomised controlled trial, aiming to recruit 78 patients over a 30-month period, from 10 centres in the UK. Patients will be randomised to either the standard arm which is a second CT-guided biopsy, or the interventional arm, a positron emission tomography-CT scan followed by a targeted CT-guided biopsy. Patients will be followed up for 12 months (patients recruited in the last 6 months of recruitment will have 6 months of follow-up). MPM biomarker mesothelin will be checked at baseline, 6 month and 12 month follow-up appointments where patients are able to attend these appointments. ETHICS AND DISSEMINATION: Ethical approval for this trial was granted by the South West—Exeter research and ethics committee (reference number 15/SW/0156). Results of the trial will be published in a peer-reviewed journal and presented at an international conference. TRIAL REGISTRATION NUMBER: ISRCTN14024829; Pre-results.